Porous fiber membrane with multi-stage pore channel structure and preparation method of porous fiber membrane

By injecting a mixed solution of soluble polymer and EVOH nanofibers into a non-solvent solidification bath containing a crosslinking agent, a porous fiber dispersion is formed and aiding film formation, the existing porous fiber membrane material has been solved by injecting a mixed solution of soluble polymer and EVOH nanofibers into a non-solvent solidification bath containing a crosslinking agent to form a porous fiber dispersion and assisting in film formation. The existing porous fiber membrane material has a single structure and complex preparation. Problem, efficient preparation and efficient adsorption and separation performance of porous fiber membranes with multi-stage pore structures are achieved.

CN119386683AActive Publication Date: 2025-02-07WUHAN TEXTILE UNIV +1

Patent Information

Application Number
CN202411550414.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing porous fiber membrane material has a single structure, which cannot meet the application needs of efficient adsorption and separation. At the same time, the preparation process is complex and it is difficult to achieve large-scale production.

Method used

Using a mixed solution of soluble polymer and EVOH nanofibers, it is injected into a rotating stirred non-solvent solidification bath containing crosslinking agent through a syringe, and a porous fiber dispersion is formed by centrifugal force, and the film is assisted under the action of negative pressure. After drying, A porous fiber membrane with a multi-stage pore structure is obtained.

Benefits of technology

The preparation of a porous fiber membrane with a multi-stage pore structure has been realized. The fiber membrane has micro-scale pores inside and nano-scale pores on the surface, which reduces the mass transfer resistance of molecules, ions, particles and other substances, improves the load capacity and adsorption and separation efficiency. Suitable for the isolation and purification of biological macromolecules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386683A_ABST
    Figure CN119386683A_ABST
Patent Text Reader

Abstract

The invention provides a porous fiber membrane with a multistage pore channel structure and a preparation method thereof.The preparation method comprises the steps that soluble polymers are dissolved in corresponding solvents, then dispersed EVOH nanofibers are added, and a mixed solution of the polymer solution and the EVOH nanofibers is obtained; injecting the mixed solution into a rotationally stirred non-solvent coagulating bath containing a cross-linking agent at a certain rate by using an injector, performing phase separation on the mixed solution, forming porous fibers under the action of centrifugal force, and dispersing the porous fibers in a non-solvent to obtain a porous fiber dispersion liquid; and finally, coating the porous fiber dispersion liquid on a non-woven base material, performing auxiliary film formation under the action of negative pressure, and drying to obtain the porous fiber film with the multilevel pore channel structure. The prepared porous fiber membrane with the hierarchical porous channel structure not only has micron-sized porous channels, but also has nano-sized porous channels with different sizes on the surfaces of the porous fibers forming the membrane channels, shows higher loading capacity and lower mass transfer resistance, and is suitable for the field of adsorption separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fiber membrane material preparation, and in particular to a porous fiber membrane with a multi-level pore structure and a preparation method thereof. Background Art

[0002] Porous fiber membrane filter materials have the advantages of large specific surface area, high porosity, small pore size, and good internal pore connectivity, which makes them have excellent adsorption and separation performance. At present, ordinary fiber membrane materials have a single structure, and their specific surface area and porosity cannot meet the application requirements of efficient adsorption and separation.

[0003] The invention patent (CN 116791225 A) discloses a super-tough cellulose aerogel fiber and its preparation method and application. The preparation method includes using wet spinning technology to prepare a cellulose molecular solution using cellulose polymer as raw material; then using the cellulose molecular solution as spinning liquid, the cellulose polymer undergoes in-situ self-assembly and hydrogen bond cross-linking reaction during the spinning process to form a multi-level nanofiber structure; the nanofiber structure is a continuous three-dimensional multi-level pore network structure. The cellulose aerogel fiber prepared by this scheme not only has excellent physical properties such as high strength and high toughness, but also has good adsorption and thermal insulation properties due to its multi-level pore structure, so that it can be used not only in the field of weaving technology, but also in the field of air purification, heavy metal adsorption, atmospheric inhalable particulate adsorption, indoor harmful gas adsorption, filter material or thermal insulation material technology, and can be widely used. However, the porous fiber prepared by the above method is relatively coarse and difficult to use alone, and needs to be further processed into a fabric material.

[0004] The invention patent (CN 111676591 A) discloses a graphene oxide aerogel fiber fabric and its preparation method and application. The preparation method comprises the following steps: dispersing graphene oxide in a solvent, oscillating and mixing, and ultrasonically obtaining a graphene oxide solution; injecting the obtained graphene oxide solution into a rotating coagulation bath through a spinning head, washing with deionized water after coagulation, and obtaining graphene oxide gel fiber; taking the obtained graphene oxide gel fiber, filtering to obtain gel fiber fabric, and then freeze-drying to obtain graphene oxide aerogel fiber fabric. The product obtained by this method has a multi-level pore structure formed by nano-scale voids and micron-scale holes, high filtration efficiency, good PM2.5 capture performance, and has broad application prospects in the field of air filtration. However, the preparation process of the above method is complicated, freeze-drying is required, and it is difficult to achieve large-scale preparation and production.

[0005] In view of this, it is necessary to design an improved multi-level pore structure porous fiber membrane and a preparation method thereof to solve the above problems. Summary of the invention

[0006] The object of the present invention is to provide a porous fiber membrane with a multi-level pore structure and a preparation method thereof. The preparation method comprises the following steps: dissolving a soluble polymer into a corresponding solvent, and then adding dispersed EVOH nanofibers to obtain a polymer solution; injecting the polymer solution into a rotating and stirring non-solvent coagulation bath containing a cross-linking agent using a syringe at a certain rate, causing the mixed solution to undergo phase separation, and forming porous fibers dispersed in the non-solvent under the action of centrifugal force to obtain a porous fiber dispersion; finally, coating the aforementioned porous fiber dispersion on a non-woven substrate, assisting film formation under the action of negative pressure, and obtaining a porous fiber membrane with a multi-level pore structure after drying.

[0007] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing a porous fiber membrane with a multi-level pore structure, comprising the following steps:

[0008] S1, dissolving a soluble polymer into a corresponding solvent to obtain a polymer solution with a mass fraction of 1-10%;

[0009] S2, adding the dispersed EVOH nanofibers to the polymer solution obtained in step S1, and stirring for 10-30 minutes using an emulsifier to obtain a uniformly dispersed mixed solution;

[0010] S3, injecting the mixed solution obtained in step S2 into a non-solvent coagulation bath containing a cross-linking agent that is rotating and stirring at a certain rate using a syringe, so that the mixed solution undergoes phase separation and forms porous fibers dispersed in the non-solvent under the action of centrifugal force, thereby obtaining a porous fiber dispersion;

[0011] S4, coating the porous fiber dispersion obtained in step S3 on a nonwoven substrate, assisting film formation under negative pressure, and drying to obtain a porous fiber membrane with a multi-level pore structure.

[0012] Furthermore, in step S3, the injection rate of the syringe is 10-100 mm / min, and the stirring rate of the coagulation bath is 100-1000 rpm.

[0013] Furthermore, in step S3, the non-solvent coagulation bath is one of ethanol and isopropanol, and the cross-linking agent is glutaraldehyde.

[0014] Furthermore, in step S2, the EVOH nanofibers have a diameter distribution of 50-500 nm and an average diameter of 100 nm.

[0015] Furthermore, in step S2, the EVOH nanofiber content is 0.1%-5%.

[0016] Furthermore, in step S3, the solid content of the fibers in the porous fiber dispersion is 0.5% to 10%.

[0017] Furthermore, in step S1, the soluble polymer is one of polyethersulfone, polyvinyl alcohol, nylon, cellulose ester, chitosan, quaternized chitosan, and sodium alginate; and the solvent is one of acetone, water, and dimethylformamide.

[0018] The present invention also provides a multi-level pore structure porous fiber membrane, which is prepared by the preparation method of the multi-level pore structure porous fiber membrane described in any one of the above. The multi-level pore structure porous fiber membrane is composed of porous fibers with a diameter of 10-100 μm, and the porous fibers are composed of nanofibers and porous polymer fibers intertwined with each other; the fiber membrane has micron-scale pores inside, and the porous fiber surface has nanoscale pores.

[0019] Furthermore, the pores inside the fiber membrane are formed by accumulation of wet-laid porous fibers, and the pore diameter ranges from 1 to 100 μm. The pores on the surface of the wet-laid porous fibers are composed of porous polymers and nanofibers, and the pore diameter ranges from 100 to 500 nm.

[0020] Furthermore, the thickness of the multi-level pore structure porous fiber membrane is 10-100 μm; the diameter range of the nanofiber is 50-500 nm.

[0021] The prepared multi-level pore structure porous fiber membrane not only has micron-scale pores (1-100μm), but also the porous fiber surface constituting the membrane pores has nanoscale pores (100-500nm) of varying sizes, which effectively reduces the mass transfer resistance of molecules, ions, particles and other substances therein. This multi-level pore structure exhibits higher load capacity and lower mass transfer resistance, and is suitable for the field of adsorption and separation, realizing stable and efficient adsorption and separation of biological macromolecules.

[0022] The beneficial effects of the present invention are:

[0023] 1. The preparation method of the multi-level pore structure porous fiber membrane of the present invention is as follows: firstly, a soluble polymer is dissolved in a corresponding solvent, and then the dispersed EVOH nanofibers are added to obtain a polymer solution; then, a syringe is used to inject the polymer solution into a rotating and stirring non-solvent coagulation bath containing a cross-linking agent at a certain rate, and the mixed solution undergoes phase separation, and porous fibers are formed under the action of centrifugal force and dispersed in the non-solvent to obtain a porous fiber dispersion; finally, the aforementioned porous fiber dispersion is coated on a non-woven substrate, and the film is assisted under the action of negative pressure, and a porous fiber membrane with a multi-level pore structure can be obtained after drying. The preparation method is simple, without cumbersome preparation processes and complex chemical reactions. It only needs to inject the mixture of polymer and EVOH nanofiber into a coagulation bath, and porous fibers can be formed under the action of centrifugal force, and the porous fiber membrane can be obtained after filtration.

[0024] 2. The multi-level pore structure porous fiber membrane prepared by the present invention not only has micron-level pores (1-100 μm) inside the fiber membrane, but also has pores inside the fiber membrane formed by fiber stacking. In addition, the fiber surface constituting the membrane pores has many nano-level pores (100-500 nm) of different sizes. That is, the fiber membrane has a multi-level pore structure, which effectively reduces the mass transfer resistance of molecules, ions, particles and other substances therein. This multi-level pore structure shows higher load capacity and lower mass transfer resistance, and is suitable for the field of separation, purification, adsorption and separation of biomacromolecules. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The surface and cross-sectional morphology of the CAB+EVOH nanofiber porous fiber obtained in step S3 of Example 1.

[0026] Figure 2 The surface and cross-sectional morphology of the CAB+EVOH nanofiber porous fiber membrane prepared in Example 1.

[0027] Figure 3 The surface and cross-sectional morphology of the porous PES+EVOH nanofiber obtained in step S3 of Example 2.

[0028] Figure 4 The surface and cross-sectional morphology of the PA6+EVOH nanofiber porous fiber obtained in step S3 of Example 4.

[0029] Figure 5 The surface and cross-sectional morphology of the chitosan + EVOH nanofiber porous fiber obtained in step S3 of Example 5.

[0030] Figure 6 The surface and cross-sectional morphology of the porous fibers of sodium alginate + EVOH nanofibers obtained in step S3 of Example 7.

[0031] Figure 7 This is the surface morphology of the CAB+EVOH nanofiber porous fiber obtained in step S3 of Comparative Example 1.

[0032] Figure 8 This is the surface morphology of the CAB porous fiber obtained in Comparative Example 2.

[0033] Fig. 9 This is the surface morphology of the CAB+EVOH nanofiber porous membrane (without coagulation bath) obtained in Comparative Example 3. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.

[0036] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0037] The present invention provides a method for preparing a porous fiber membrane with a multi-level pore structure, comprising the following steps:

[0038] S1, dissolving a soluble polymer into a corresponding solvent to obtain a polymer solution with a mass fraction of 1-10%;

[0039] Specifically, the soluble polymer is one of polyethersulfone, polyvinyl alcohol, nylon, cellulose esters, chitosan, quaternized chitosan, and sodium alginate. Cellulose esters may be cellulose acetate butyrate, cellulose acetate propionate, and cellulose acetate.

[0040] The solvent is one of acetone, water and dimethylformamide.

[0041] S2, adding the dispersed EVOH nanofibers to the polymer solution obtained in step S1, and stirring for 10-30 minutes using an emulsifier to obtain a uniformly dispersed mixed solution;

[0042] Specifically, the diameter distribution of EVOH nanofibers is 50-500 nm, and the average diameter is 100 nm.

[0043] The content of EVOH nanofiber is 0.1%-5% of the mass fraction of the polymer solution.

[0044] S3, injecting the mixed solution obtained in step S2 into a non-solvent coagulation bath containing a cross-linking agent that is rotating and stirring at a certain rate using a syringe, so that the mixed solution undergoes phase separation and forms porous fibers dispersed in the non-solvent under the action of centrifugal force, thereby obtaining a porous fiber dispersion;

[0045] Specifically, the non-solvent coagulation bath is one of ethanol and isopropanol, and the cross-linking agent is glutaraldehyde.

[0046] The injection rate of the syringe is 10-100 mm / min, and the stirring rate of the coagulation bath is 100-1000 rpm.

[0047] The solid content of the fibers in the porous fiber dispersion is 0.5% to 10%.

[0048] During this process, when the mixed solution is injected into the coagulation bath, it is stretched under the action of centrifugal force to form fibers. At the same time, the solvent in the mixed solution and the non-solvent in the coagulation bath undergo double diffusion, the polymer phases are separated, and a large number of through-holes are formed inside and on the surface. EVOH nanofibers are interspersed in the porous fibers to form a skeleton structure, and together with the polymer constitute porous fibers.

[0049] S4, coating the porous fiber dispersion obtained in step S3 on a nonwoven substrate, assisting film formation under negative pressure, and drying to obtain a fiber membrane with a multi-level pore structure.

[0050] The present invention also provides a multi-level pore structure porous fiber membrane, which is prepared by the above-mentioned preparation method of the multi-level pore structure porous fiber membrane. The multi-level pore structure porous fiber membrane is composed of porous fibers with a diameter of 10-100 μm, and the porous fibers are composed of nanofibers and porous polymer fibers intertwined with each other; the fiber membrane has micron-scale pores inside, and the porous fiber surface has nanoscale pores.

[0051] The pores inside the fiber membrane are formed by the accumulation of wet-process porous fibers, with a pore diameter ranging from 1 to 100 μm. The pores on the surface of the wet-process porous fibers are composed of porous polymers and nanofibers, with a pore diameter ranging from 100 to 500 nm.

[0052] The thickness of the multi-level pore structure porous fiber membrane is 10-100 μm.

[0053] The nonwoven substrate is polypropylene nonwoven fabric.

[0054] The porous fiber membrane material has a multi-level pore structure on the one hand, and has a high porosity and specific surface area on the other hand, which is beneficial to its adsorption and separation performance. The multi-level pore structure porous fiber membrane can be used for the adsorption and separation of biomacromolecules.

[0055] The multi-level pore structure porous fiber membrane and the preparation method thereof provided by the present invention are described below with reference to specific embodiments.

[0056] Example 1

[0057] This embodiment provides a method for preparing a porous fiber membrane with a multi-level pore structure, comprising the following steps:

[0058] S1, dissolving cellulose acetate butyrate (CAB) in acetone to obtain a CAB solution with a mass fraction of 5%;

[0059] S2, placing the monodispersed EVOH nanofibers in the CAB solution obtained in step S1, and stirring for 30 minutes using an emulsifier to uniformly disperse the EVOH nanofibers in the CAB solution to obtain a mixed solution; wherein the mass fraction of the EVOH nanofibers is 0.5%;

[0060] The preparation method of monodisperse EVOH nanofibers is as follows:

[0061] The EVOH nanofibers are prepared by a melt extrusion phase separation method; then, the EVOH nanofibers are dispersed in a mixed solvent to obtain an EVOH nanofiber dispersion; after removing the mixed solvent, monodispersed EVOH nanofibers are obtained.

[0062] The mixed solvent is ethanol and water in a mass ratio of 1:1; the diameter of the EVOH nanofiber is 100 nm.

[0063] S3, injecting the mixed solution obtained in step S2 into the isopropanol solution at a rate of 5 mm / min using a syringe (the syringe needle is 0.2 mm);

[0064] The stirring rate of the isopropanol solution is 200 r / min. At this time, CAB undergoes phase separation in the isopropanol and forms fibers dispersed in the isopropanol under the action of centrifugal force to obtain a porous fiber dispersion.

[0065] S4, coating the porous fiber dispersion obtained in step S3 on a nonwoven substrate, assisting film formation under negative pressure, and peeling it off from the nonwoven substrate after drying to obtain a fiber membrane with a multi-level pore structure.

[0066] See also Figure 1 The figure shows the surface and cross-sectional morphology of the CAB+EVOH nanofiber porous fiber obtained in step S3 of Example 1. Figure 1 (a) and (b) are SEM images of the fiber surface. Figure 1 (c) and (d) are SEM images of the fiber cross section. The fiber diameter ranges from 10 to 100 μm.

[0067] It can be seen that there are many small holes (20-100nm) of different sizes on the fiber surface. In addition, from the cross-section of the fiber, it can be seen that these channels are not only present on the fiber surface, but also penetrate and connect the entire fiber.

[0068] See also Figure 2 The figure shows the surface and cross-sectional morphology of the CAB+EVOH nanofiber porous fiber membrane obtained in step S4 of Example 1. Figure 2 (a) and (b) are SEM images of the fiber membrane surface. Figure 2(c) and (d) are SEM images of the cross section of the fiber membrane.

[0069] It can be seen that the membrane is composed of fibers of varying thicknesses, presenting a typical nonwoven structure. In addition, from the surface and cross-sectional morphology, it can be seen that the fibers are stacked to form 10-100μm channels, and there are 20-100nm channels inside the fibers, forming a multi-level channel structure.

[0070] Examples 2-5 and Comparative Example 1

[0071] Examples 2-5 and Comparative Example 1 provide a method for preparing a porous fiber membrane with a multi-level pore structure. Compared with Example 1, the difference is that the type of soluble polymer and the corresponding solvent and the concentration of the corresponding polymer solution in step S1 are changed, as shown in the following table. The rest is roughly the same as Example 1 and will not be repeated here.

[0072] Types of soluble polymers Solvents Concentration of polymer solution Example 1 CAB acetone 5% Example 2 Polyethersulfone DMF 5% Example 3 Polyvinyl alcohol 80℃ water 10% Example 4 Nylon 6 Formic acid 10% Example 5 Chitosan 1% hydrochloric acid 1.5% Example 6 Quaternized Chitosan water 2% Example 7 Sodium alginate water 1% Comparative Example 1 CAB acetone 15%

[0073] Experiments show that embodiments 2-7 can produce porous fiber membranes with multi-level pore structures. Figure 3-6 shown.

[0074] Figure 7 The surface morphology of the CAB+EVOH nanofiber porous fiber obtained in step S3 of comparative example 1. It can be seen that when the concentration of the polymer solution exceeds a certain concentration range, the mixed solution of high-concentration CAB and EVOH nanofibers is difficult to form a fibrous multi-level pore structure, and a porous structure in which CAB particles are docked is formed, and the specific surface area and porosity are lower than those of the fibrous pore structure.

[0075] Comparative Example 2

[0076] Comparative Example 2 provides a method for preparing a porous fiber membrane with a multi-level pore structure. Compared with Example 1, the difference is that step S2 is not performed, that is, EVOH nanofibers are not added. The rest is roughly the same as Example 1 and will not be repeated here.

[0077] like Figure 8 As shown, without adding EVOH nanofibers, the polymer solution forms a conventional porous structure under the action of non-solvent phase separation, and without the support of the fiber skeleton, its strength is poor and the stability of the structure cannot be maintained.

[0078] Comparative Example 3

[0079] Comparative Example 3 provides a multi-level pore structure porous fiber membrane and a preparation method thereof. Compared with Example 1, the difference is that the coagulation bath treatment in step S3 is not performed, that is, the mixed solution is directly coated on the non-woven substrate. The rest is roughly the same as Example 1 and will not be repeated here.

[0080] like Fig. 9 The figure shows the surface morphology of the CAB+EVOH nanofiber porous membrane obtained in this comparative example. Without the bidirectional diffusion effect of the coagulation bath, during the natural drying process, the CAB solution and the EVOH nanofiber mixed solution cannot form a porous structure, but a flat plate structure with extremely low specific surface area and porosity and no through-network is formed, and a fiber membrane material composed of porous fibers cannot be obtained.

[0081] Comparative Example 4

[0082] Comparative Example 4 provides a method for preparing a porous fiber membrane with a multi-level pore structure. Compared with Example 1, the difference is that in step S3, the non-solvent coagulation bath is not stirred, and the rest is roughly the same as Example 1 and will not be repeated here.

[0083] Experiments show that when the mixed solution is injected into the coagulation bath without stirring, it cannot be stretched and thinned under the action of centrifugal force. The formed fibers are coarse and difficult to disperse in the coagulation bath, and the film material cannot be prepared by the non-woven method.

[0084] Comparative Example 5

[0085] Comparative Example 5 provides a porous fiber membrane with a multi-level pore structure and a preparation method thereof. Compared with Example 1, the difference is that in step S3, the cross-linking agent is changed from glutaraldehyde to citric acid, and the rest is roughly the same as Example 1 and will not be repeated here.

[0086] Experiments show that without the cross-linking effect of glutaraldehyde, the fiber strength is poor, it is very easy to break, and it is difficult to maintain integrity.

[0087] Comparative Example 6

[0088] Comparative Example 6 provides a porous fiber membrane with a multi-level pore structure and a preparation method thereof. Compared with Example 1, the difference is that in step S3, no cross-linking agent is added, and the rest is roughly the same as Example 1, which will not be repeated here.

[0089] Experiments show that without the cross-linking effect of glutaraldehyde, the fiber strength is poor, it is very easy to break, and it is difficult to maintain integrity.

[0090] Comparative Example 7

[0091] Comparative Example 7 provides a multi-level pore structure porous fiber membrane and a preparation method thereof. Compared with Example 1, the difference is that in step S3, the injection rate of the syringe is 200 mm / min, and the rest is roughly the same as Example 1, which will not be repeated here.

[0092] Experiments show that when the injection rate is too fast, the mixed solution forms irregularly shaped substances in the coagulation bath and cannot form fibers.

[0093] The fiber membranes prepared in Examples 1-7 and Comparative Examples 1-7 were tested for pore size statistics, mechanical properties, and filtration performance, and the results are shown in the following table.

[0094] The test process is: put 0.05g of membrane sample into 100ml (2g / L) protein solution and shake at 150rpm for 24 hours at room temperature. After shaking, take out the membrane. Test the concentration change of protein solution before and after adsorption, and the adsorption capacity of the membrane is calculated by the following formula:

[0095]

[0096] In the formula, q t is the protein adsorption capacity of the membrane in time t;

[0097] C 0 is the concentration of protein in the solution before adsorption;

[0098] C t is the concentration of protein in the solution after adsorption;

[0099] m is the mass of the membrane sample.

[0100] The test results are as follows:

[0101]

[0102]

[0103] As shown in the table above, it can be seen from Examples 1-7 that different polymers can be used to prepare multi-level porous fibers with high specific surface area and high porosity under this method, and can adsorb corresponding biomacromolecules according to the functional groups carried by the polymer itself.

[0104] It can be seen from Comparative Example 1 that when the concentration of the polymer (CAB) is too high, the multi-level pores formed are not composed of fibers but of particles, and their specific surface area and porosity are reduced, resulting in a decrease in their adsorption capacity for biomacromolecules.

[0105] It can be seen from Comparative Example 2 that a porous fiber membrane can still be prepared without EVOH nanofibers, but due to the lack of nanofibers to provide a cross-linked network skeleton, the strength of the fiber membrane is poor, and it is difficult to maintain its structural integrity in water, making it difficult to perform adsorption applications.

[0106] It can be seen from Comparative Example 3 that the mixed solution is directly coated on the nonwoven substrate without the action of a coagulation bath to form a flat membrane without any void structure, and its adsorption capacity is very poor.

[0107] It can be seen from Comparative Example 4 that the mixed solution is injected into the coagulation bath without stirring, and cannot be stretched and thinned under the action of centrifugal force. The formed fibers are relatively coarse, and the specific surface area and porosity of the prepared fiber membrane are lower than those of the fiber membrane in Example 1, thus showing relatively poor adsorption capacity.

[0108] It can be seen from Comparative Example 5 that after the cross-linking agent is replaced by citric acid from glutaraldehyde, the strength of the prepared fiber membrane is poor, and due to the effect of the carboxyl group of citric acid, it has a certain adsorption effect on lysozyme.

[0109] It can be seen from Comparative Example 6 that without the action of a cross-linking agent, the fiber membrane has low strength and cannot maintain structural integrity.

[0110] It can be seen from Comparative Example 7 that when the injection rate of the mixed solution is too fast, the mixed solution forms a substance of irregular shape in the coagulation bath, and a fiber membrane cannot be prepared.

[0111] In summary, the present invention provides a multi-level pore structure porous fiber membrane and a preparation method thereof. The preparation method dissolves a soluble polymer into a corresponding solvent, then adds the dispersed polymer nanofibers to obtain a polymer solution; then uses a syringe to inject the polymer solution into a rotating and stirring non-solvent coagulation bath containing a cross-linking agent at a certain rate, the mixed solution undergoes phase separation, and under the action of centrifugal force, fibers are formed and dispersed in the non-solvent to obtain a fiber dispersion liquid; finally, the aforementioned fiber dispersion liquid is coated on a non-woven substrate, and the film is assisted to form under the action of negative pressure, and a fiber membrane with a multi-level pore structure can be obtained after drying. The obtained multi-level pore structure porous fiber membrane not only has micron-scale pores (1-100μm) inside the fiber membrane, but also has many nano-scale pores (100-500nm) of different sizes on the fiber surface constituting the membrane pores, which effectively reduces the mass transfer resistance of molecules, ions, particles and other substances therein. This multi-level pore structure exhibits higher load capacity and lower mass transfer resistance, and is suitable for the field of separation, purification, adsorption and separation of biomacromolecules.

[0112] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a porous fiber membrane with a multi-level pore structure, characterized in that: The following steps are involved: S1, dissolving a soluble polymer into a corresponding solvent to obtain a polymer solution with a mass fraction of 1-10%; S2, adding the dispersed EVOH nanofibers to the polymer solution obtained in step S1, and stirring for 10-30 minutes using an emulsifier to obtain a uniformly dispersed mixed solution; S3, injecting the mixed solution obtained in step S2 into a non-solvent coagulation bath containing a cross-linking agent that is rotating and stirring at a certain rate using a syringe, so that the mixed solution undergoes phase separation and forms porous fibers dispersed in the non-solvent under the action of centrifugal force, thereby obtaining a porous fiber dispersion; S4, coating the porous fiber dispersion obtained in step S3 on a nonwoven substrate, assisting film formation under negative pressure, and drying to obtain a porous fiber membrane with a multi-level pore structure.

2. The method for preparing a porous fiber membrane with a multi-level pore structure according to claim 1, characterized in that: In step S3, the injection rate of the syringe is 10-100 mm / min, and the stirring rate of the coagulation bath is 100-1000 rpm.

3. The method for preparing a porous fiber membrane with a multi-level pore structure according to claim 1, characterized in that: In step S3, the non-solvent coagulation bath is one of ethanol and isopropanol, and the cross-linking agent is glutaraldehyde.

4. The method for preparing a porous fiber membrane with a multi-level pore structure according to claim 1, characterized in that: In step S2, the EVOH nanofibers have a diameter distribution of 50-500 nm and an average diameter of 100 nm.

5. The method for preparing a porous fiber membrane with a multi-level pore structure according to claim 4, characterized in that: In step S2, the EVOH nanofiber content is 0.1-5wt%.

6. The method for preparing a porous fiber membrane with a multi-level pore structure according to claim 1, characterized in that: In step S3, the solid content of the fibers in the porous fiber dispersion is 0.5% to 10%.

7. The method for preparing a porous fiber membrane with a multi-level pore structure according to claim 1, characterized in that: In step S1, the soluble polymer is one of polyethersulfone, polyvinyl alcohol, nylon, cellulose ester, chitosan, quaternized chitosan, and sodium alginate; and the solvent is one of acetone, water, and dimethylformamide.

8. A porous fiber membrane with a multi-level pore structure, characterized in that: Prepared by the preparation method described in any one of claims 1-7; the multi-level pore structure porous fiber membrane is composed of porous fibers with a diameter of 10-100μm, and the porous fibers are composed of nanofibers and porous polymer fibers intertwined with each other; the fiber membrane has micron-scale pores inside, and the porous fiber surface has nanoscale pores.

9. The multi-level pore structure porous fiber membrane according to claim 8, characterized in that: The pores inside the fiber membrane are formed by the accumulation of wet-laid porous fibers, and the pore diameter ranges from 1 to 100 μm. The pores on the surface of the wet-laid porous fibers are composed of porous polymers and nanofibers, and the pore diameter ranges from 100 to 500 nm.

10. The porous fiber membrane with a multi-level pore structure according to claim 8, characterized in that: The thickness of the multi-level pore structure porous fiber membrane is 10-100 μm; the diameter range of the nanofiber is 50-500 nm.

Citation Information

Patent Citations

  • Graphene oxide aerogel fiber fabric as well as preparation method and application thereof

    CN111676591A

  • Super-tough cellulose aerogel fiber as well as preparation method and application thereof

    CN116791225A

  • Bacterial cellulose nanofiber composite membrane for efficient protein adsorption and separation and preparation method of composite membrane

    CN107413316A

  • Preparation method of graphene / polyaniline / EVOH nanofiber composite membrane

    CN109423045A

  • Nanofiber chitosan porous material and preparation method thereof

    CN110982124A

Cited By

  • Nanofiber membrane for CO2 reduction as well as preparation method and application of nanofiber membrane

    CN121538684A

  • Hierarchical porous sodium alginate nanofiber aerogel as well as preparation method and application thereof

    CN122465210A